2008
DOI: 10.1007/s00216-008-2045-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrically detected displacement assay (EDDA): a practical approach to nucleic acid testing in clinical or medical diagnosis

Abstract: This paper introduces the electrically detected displacement assay (EDDA), a electrical biosensor detection principle for applications in medical and clinical diagnosis, and compares the method to currently available microarray technologies in this field. The sensor can be integrated into automated systems of routine diagnosis, but may also be used as a sensor that is directly applied to the polymerase chain reaction (PCR) reaction vessel to detect unlabeled target amplicons within a few minutes. Major aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 35 publications
1
48
0
1
Order By: Relevance
“…Using covalent ferrocene labels, Hartwich et al also found similar melting behavior [34]. The effect of the osmium marker upon the melting temperature should be small since the double stranded section did not contain labeled bases.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Using covalent ferrocene labels, Hartwich et al also found similar melting behavior [34]. The effect of the osmium marker upon the melting temperature should be small since the double stranded section did not contain labeled bases.…”
Section: Resultsmentioning
confidence: 83%
“…However, these first approaches either required sophisticated probe-SAM design on the electrode or difficult calculation of very small signal current differences, which were depending upon the hybridization temperature. More promising are approaches basing upon covalent DNA labels such as ferrocene and osmium(II) complexes, which are, however, costly modifications [34].…”
Section: Introductionmentioning
confidence: 99%
“…6B). This may result from insufficient removal of nonspecifically adsorbed cDNA molecules or nonselective detachment of cDNA molecules due to the relatively weak bond between thiol and gold [19]. The nonselective recovery of genetic molecules from a chip causes a noise of selected genetic information and disturbs an efficient selection of functional biomolecules.…”
Section: Photorecovery and Amplification Of Cdnamentioning
confidence: 99%
“…Particularly, SiNWs have recently attracted attention in the research community due to label-free detection with scope for mass production, multi detection, CMOS compatibility and portability [5]. Contemporary DNA sensors employ optical readout techniques and use labels for hybridization thus making them expensive and bulky [6]. By eliminating optical readout-hybridization techniques and enabling direct electrical detection it is possible to make DNA sensing label free.…”
Section: Introductionmentioning
confidence: 99%